Survei System Quality Aplikasi Transportasi Online Gojek dan Grab - Charles Tambunan; Primasatria Edastama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The reason of this consider is to assess the framework quality of Gojek and Grab online transportation applications in terms of behavioral purposeful to utilize, quality of data, seen ease of utilize, seen value and client fulfillment to find out whether there's . The approach to this think about is to use quantitative inquire about. Purposive sampling in sampling in research, the sample size is determined using the formula 5x of the number of Likert scale questions 1 - 5 available, so 135 respondents participated in this study. The test populace comprises of clients who have requested the Gojek and Grab online transportation applications for at slightest one year and utilize them at slightest twice a week, and the user come from generation Z. The quantitative overview information collected summed to 196 respondents. The information investigation strategy in this think about employments Basic Condition Modeling - Fractional Slightest Squares (SEM-PLS) utilizing the SmartPLS 4.0 and IBM SPSS 29 data processing and distribution applications. The comes about of this ponder show that quality of data, seen ease of utilize and seen value have a positive impact on behavioral deliberate to utilize in utilizing data. And framework quality includes a positive affect on behavioral deliberate to utilize. The trade suggestion of this inquire about is to make strides the quality of the online transportation application framework of Gojek and Grab, so that ease of utilize can be consolidated into the creation of a higher client interface within the future.